1985
DOI: 10.1093/nar/13.7.2305
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the structure of echinomycin and triostin A complexed to a DNA fragment

Abstract: Two members of the quinoxaline antibiotic family, echinomycin and triostin A, form crystals complexed to a DNA fragment with the sequence d(CpGpTpApCpG). The crystal structure of both complexes was solved by X-ray diffraction to near-atomic resolution. The two structures are similar to each other with differences in some details due to the shorter cross bridge of echinomycin. Both molecules act as bis intercalators surrounding the d(CpG) sequence at either end of the double helix. Alanine forms sequence-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
192
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(209 citation statements)
references
References 15 publications
14
192
3
Order By: Relevance
“…Most binding studies have been performed with [N-MeCys$, NMeCys(]TANDEM rather than with TANDEM itself, but the two synthetic drugs appear equivalent in terms of binding strength and specificity. Several structures of triostin A, TAN-DEM and [N-MeCys$, N-MeCys(]TANDEM bound to short duplex oligonucleotides have been elucidated by crystallography and NMR [18][19][20][21][22][23][24][25]. In general, the bis-intercalated complexes are comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Most binding studies have been performed with [N-MeCys$, NMeCys(]TANDEM rather than with TANDEM itself, but the two synthetic drugs appear equivalent in terms of binding strength and specificity. Several structures of triostin A, TAN-DEM and [N-MeCys$, N-MeCys(]TANDEM bound to short duplex oligonucleotides have been elucidated by crystallography and NMR [18][19][20][21][22][23][24][25]. In general, the bis-intercalated complexes are comparable.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray crystallography has served as the primary vehicle for elucidating the nonbonded interactions between the host nucleic acid and guest molecules (3) that include water (4), linked heterocycles [e.g., netropsin (5), echinomycin (6)], fused aromatics [e.g., triostin A (7), daunomycin (8)], and peptides [e.g., trp repressor (9), phage 434 Cro (10)]. NMR spectroscopy (11) and molecular modeling (12) have contributed additional understanding into these systems and others that have not yielded to the demands of the former technique.…”
mentioning
confidence: 99%
“…As judged by detailed X-ray, NMR structural, and other biophysical studies of these molecules, heteroaromatic planar chromophores, the invariant feature of quinomycin antibiotics, provide these compounds with the ability to bis-intercalate tightly into DNA. [52][53][54] In addition, a comparative study of echinomycin and SW-163D [55][56][57][58] found that the type of chromophore in the compounds influences their sequence selectivity. 59) However, the cyclic peptide backbone of these molecules, while providing a rigid framework that holds the chromophores in place for effective DNA intercalation, also plays an important role in determining the binding sequence specificity of these antibiotics, primarily by forming hydrogen bonds with the base moieties in the minor groove.…”
Section: Echinomycin a Dna Bis-intercalating Nonribosomal Peptidmentioning
confidence: 99%
“…59) However, the cyclic peptide backbone of these molecules, while providing a rigid framework that holds the chromophores in place for effective DNA intercalation, also plays an important role in determining the binding sequence specificity of these antibiotics, primarily by forming hydrogen bonds with the base moieties in the minor groove. [52][53][54] Furthermore, modification of the cross-bridge provides further finetuning of the binding site selectivity of these quinomycin antibiotics. This was illustrated by DNA-binding studies on echinomyicn and its close relative, triostin A.…”
Section: Echinomycin a Dna Bis-intercalating Nonribosomal Peptidmentioning
confidence: 99%